Analysing higher educational institutions' role in fulfilling their third mission - S. A. Odei; Henry Junior Anderson (REGION, 2021)
The transitional role of higher educational institutions encourages attention to initiatives aimed at positioning these institutions as hubs of knowledge production and transfers capable of influencing regional development. Nonetheless, the literature has defied the extent to which these institutions have well-embraced their third mission of impacting regional development, thus calling for further approaches in examining the role of these institutions. This paper evaluates the various ways higher educational institutions have embraced their third mission of contributing to regional development. We sourced data containing information from 164 Higher Education Institutions (HEIs) located across the United Kingdom employing the propensity score matching estimation model. The results of the Average Treatment Effects (ATE) highlight the additionality effects of HEIs on graduate support, attracting inward investment, R&D collaborations and network facilitation. Surprisingly, our results emphasis the lack of significance in HEIs role in supporting SMEs, and knowledge exchanges. The main implication relates to the challenges in adopting initiatives that proved successful in specific universities to other higher educational settings.
Keywords: 330; Propensity scores matching; regional development; higher education institutions; knowledge transfers; third mission; United Kingdom